Sulfur-enriched alkaloids from the root of Isatis indigotica - Qinglan Guo; Chengbo Xu; Minghua Chen; Sheng Lin; Yuhuan Li; Chenggen Zhu; Jiandong Jiang; Yongchun Yang; Jiangong Shi (Elsevier, 2018)
Five new sulfur-enriched alkaloids isatithioetherins A-E (1-5), and two pairs of scalemic enantiomers (+)- and (−)-isatithiopyrin B (6a and 6b) and isoepigoitrin and isogoitrin (7a and 7b), along with the known scalemic enantiomers epigoitrin and goitrin (8a and 8b), were isolated and characterized from an aqueous extract of the Isatis indigotica roots. Their structures were determined by extensive spectroscopic data analysis, including 2D NMR and theoretical calculations of electronic circular dichroism (ECD) spectra based on the quantum-mechanical time-dependent density functional theory (TDDFT). Compounds 1-5 represent a novel group of sulfur-enriched alkaloids, biogenetically originating from stereoselective assemblies of epigoitrin-derived units. Isolation and structure characterization of 6a and 6b support the postulated biosynthetic pathways for the diastereomers 9a and 9b via a rare thio-Diels-Alder reaction. Compounds 2 and 4 showed antiviral activity against the influenza virus A/Hanfang/359/95 (H3N2, IC50 0.60 and 1.92 μmol/L) and the herpes simplex virus 1 (HSV-1, IC50 3.70 and 2.87 μmol/L), and 2 also inhibited Coxsackie virus B3 (IC50 0.71 μmol/L). KEY WORDS: Cruciferae, Isatis indigotica, Sulfur-containing alkaloids, Isatithioetherins A-E, Isatithiopyrins A and B, Isoepigoitrin, Isogoitrin, Antiviral activity